A Computational Framework to Study the Effect of Acupuncture on Obesity by Integrating Multiple Levels of Data. (17th October 2020) - Liu, Huihui; Liu, Mingjun; Jiao, Yingbo; Wei, Le; Liu, Xiaochen; Li, Dandan; Zhang, Xiaolin; Yan, Minghui; Chen, Jinming
Abstract : In this study, we evaluated the efficacy of acupuncture in the treatment of obesity by a computational framework integrating randomized controlled trials published in China and abroad. Specifically, clinical trial documents published on CNKI, VIP, Wanfang, PubMed, Embase, and the Cochrane Library from 2007-2017 were downloaded and analyzed using Stata 15.1 system. As a result, a total of 13 articles were imported and 1052 patients were included. The analyses showed that the overall effect of an acupuncture group and a control group was not significant with P > 0.01 . However, the curative effect of the acupuncture group was better than that of the diet and exercise instruction group with P < 0.01 ; the curative effect of the acupuncture group was better than that of the oral Chinese and western medicine group with P < 0.01 . In conclusion, acupuncture as a complementary alternative therapy is recommended for the treatment of obesity.